Assesment of Crop and Irrigation Water Requirements for Some Selected Crops in Northwestern Bangladesh (Global Journal of Science Frontier Research, 2017)
Currently, almost 90% of the global water consumption is caused by the irrigation activities, and more than 40% of the crops are produced under the irrigated conditions. This study is an attempt to estimate the irrigation water requirement (IWR) and crop water requirement (CWR) for some selected crops (Aus, Amon, Boro, Maize, Potato, Bean, Sugarcane, Banana, Tobacco, Wheat, Tomato, Peas, Groundnut, Peeper, Cabbage and Watermelon) in northwestern Bangladesh. Two selected districts (Dinajpur and Rangpur) and an adjacent upazila of Saidpur of Nilphamari district have been taken as a case study area. Necessary meteorological (rainfall, temperature, humidity, wind speed, sunshine hours) and crop data (crop coefficient and crop calendar) have been collected for 30 years period from 1982 to 2012. FAO CROPWATv8.0 has been applied for necessary calculation of CWR and IWR along with the developing of cropping patterns.
Keywords: irrigation water requirement (IWR); crop water requirement (CWR); crop calendar; reference evapotranspiration (ETo); FAO penmanmonteith